Optimization of Green Synthesized Black Tea Nanoparticles using Central Composite Design - Nikam, Sarika; Chaudhari, Shilpa (International Journal of Pharmaceutical Investigation)
Objectives: Traditional method of optimization is lengthy and time consuming while response surface methodology evaluates the effects of multiple factors and their interactions on one or more response variables with fewer experiments. The aim of present study is optimization of green synthesized black tea nanoparticles using central composite design. Materials and Methods: 5, 15, and 25% black tea concentrations were reacted with 5, 10, and 15 mM Silver nitrate (AgNO3). An optimization study was carried out to optimize the levels of the independent factors like concentration of extract, solution of Silver nitrate, stirring speed, and stirring time. 30 numbers of experiments were performed and evaluated for responses like particle size and % yield. Characterization of silver nanoparticle was done by UV-visible spectroscopy, zeta sizer, XRD, FTIR, FESEM, etc. Results: Nanoparticles formation was revealed by color transformation from light yellow to brown. Prepared particles were monodisperse with Z-Average: 137.8 nm, polydispersity index 0.278, and Zeta potentials 22.7 mV. Electrophoretic Mobility Mean was 0.000176 cm 22/Vs, indicating the stability of silver nanoparticle suspension. Conclusion: Optimized parameters offered by Central Composite Design were 10mM AgNO3, 10% extract of black 150 min, and 700 rpm. 3D plots revealed that the metal salt concentrations and stirring rate showed a direct relationship whereas extract concentration and stirring time showed indirect relationship with particle size. % yield was highest with mid level of solution of metal salt (A) and concentration of extract (B) Stirring time (C) and stirring speed had no impact on % yield.
Keywords: Black tea; Silver nanoparticle; Green synthesis; Central composite design; Design expert; Response surface method.